Biochemical Mechanisms Regulating Salt Tolerance in Plants (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Damage from nutritional imbalance, osmotic stress, particular ion toxicity, or a combination of these factors results in salinity, which in turn affects plant improvement, growth, and physiological and biochemical activities. The impacts of salt stress on photosynthesis vary greatly among plants. Plants growing in salinity stress experience both ionic & osmotic stress, which increases the buildup of ROS and causes secondary stresses that eventually result in oxidative damage. However, among the ROS are the extremely reactive molecules OH, along with additional species like H2O2, and O2•. Moreover, the most potent ROS implicated in the oxidative degradation of biological substrates, including carbohydrates, is •OH. Mechanisms of salt adaptation that lead to improved long-term salinity tolerance may employ either the gene products from short-term salt stress or other means for increased resistance. It is likely that enhanced salt tolerance is achieved by the enhancement, activation, or maintenance function of physiological systems that are particularly sensitive to disruption by amplified concentrations of salinization. The mechanism of enhanced tolerance for salinity stress conditions can be associated with an accumulation of enzymatic & non-enzymatic activity in addition to a higher accumulation of indirect sources compared with direct sources.